A new subspecies of Jodina rhombifolia (Santalales: Cervantesiaceae), with taxonomical considerations - Arana, Marcelo D.; Luna, María Luján (Phytotaxa, 2019)
The monotypic genus Jodina is endemic from central to south-eastern South America, where it grows from southern Bolivia and Brazil, Uruguay, to northern and central Argentina. The only species included in the genus is Jodina rhombifolia, a small hemiparasitic tree about 4–8 m high that is characteristic of the chacoan environments of the Neotropical region and Monte from the South American transition zone. As part of the floristic updates in the Neotropical and Andean regions of South America, the nomenclature of taxa related to Jodina rhombifolia was re-examined. Owing to the morphological and anatomical differences observed, and the well-delimited geographical distribution patterns that suggest the existence of two distinguishable subspecific entities, a new subspecies of Jodina rhombifolia is proposed here. Two lectotypes are designated and the nomenclature is clarified. An identification key, complete descriptions of the taxa and geographical distribution of the subspecies are also provided.